Pre-stroke Disability and Long-Term Functional Limitations in Stroke Survivors: Findings From More of 12 Years of Follow-Up Across Three International Surveys of Aging - Gil-Salcedo, Andres; Dugravot, Aline; Fayosse, Aurore; Landré, Benjamin; Jacob, Louis; Bloomberg, Mikaela; Sabia, Séverine; Schnitzler, Alexis (Frontiers in Neurology, 2022)
Background Almost 50% of the post-stroke disabled population already have a premorbid disability before stroke. These patients may be offered a different care pathway in the acute and subacute phase than those without pre-morbid disability. Therefore, the aim of this study was to assess the association of the severity of premorbid disability with change of limitations in basic and instrumental activities of daily living (ADL/IADL) 1 year after stroke and over the following decade. Methods Among 3,432 participants from HRS, SHARE and ELSA cohorts with a first stroke, ADL/IADL limitations were measured at 1–2 years prior to stroke, at 1 year post-stroke, and during the chronic phase. Modified Ranking Scale (P-mRS) was used to categorize the participants by level of premorbid disability (1–2 years pre-stroke). Change in ADL/IADL limitations by P-mRS level (0–1, 2–3, and 4–5) was assessed using a piecewise linear mixed model with a breakpoint set at 1 year post-stroke, stratified by median age groups. Results Increase in ADL limitations at 1 year post-stroke was less pronounced in P-mRS ≥2 (p < 0.005). After years of relative stability, limitations of ADL increased for all P-mRS levels (p = 0.003). In those aged ≥75 years at stroke event, the increase was similar irrespective of P-mRS (p = 0.090). There were no significant differences in IADL trajectories between P-mRS levels (p ≥ 0.127). Conclusion These results suggest similar trajectories of functional limitations between P-mRS levels up to 9 years post-stroke, highlighting the possible benefit of including patients with pre-morbid disability to certain treatments during the acute phase.